THE ROLE OF THE FRENCH INTERNATIONAL EXPEDITION IN THE DEVELOPMENT OF ARCHAEOLOGICAL RESEARCH - Farmanova Gulnara Komilevna (Galaxy International Interdisciplinary Research Journal, 2023)
The author argues that after the declaration of independence of the Republic of Uzbekistan, wide opportunities have opened up for fruitful and close scientific international cooperation in various fields, including in the field of archaeological research. Cooperation agreements between the Institute of Archeology of the Academy of Sciences of Uzbekistan and advanced research centers in France are currently of great importance for the development of archaeological science and methods of excavation.